Pulmonary Embolism in High-Risk Patients: How to Select Standard Imaging and Management Strategy? - Sidhi Laksono; Firizkita Dewi; Reynaldo Halomoan (International Journal of Integrated Health Sciences, 2021)
Objective: To describe the use of computed tomography pulmonary angiography (CTPA) for diagnostic purposes and percutaneous catheter-directed thrombolysis (PCDT) as a treatment choice for high-risk pulmonary embolism (PE) patients.Methods: This case report describes a case of an elderly female presented with dyspnea, cough, fever, and chest pain. No significant medical history was identified.Results: CTPA was conducted and showed multiple thrombus with significant stenosis in several branches of pulmonary artery. Initial anticoagulation was administered without delay. Patient then underwent PCDT to remove the thrombus. No post intervention symptom and systemic complications were noted.Conclusions: Computed tomography pulmonary angiography is useful as the standard imaging modality to help evaluating suspected pulmonary embolism. Percutaneous catheter-directed thrombolysis is indicated to treat high-risk patients with high risk of bleeding.